(untitled) (Research, Society and Development, 2020)
This study aimed to identify the potentialities and weaknesses experienced by the nurse in the daily work in the prehospital care service, as well as the perspectives of the nurses related to the future of the professional category, in this context. It is an a qualitative, exploratory-descriptive study was carried out with four nurses who worked in the prehospital care service and five residents of a Professional Residency Program in Nursing in Emergency/Trauma, who practiced in a prehospital care service in the state of Rio Grande do Sul. The data collected between August and September of 2018, through a semi-structured interview, were submitted to discursive textual analysis, resulting in three categories emerged: Fragilities experienced/perceived by nurses in Pre-Hospital Care; Potentialities experienced/perceived by nurses in Pre-Hospital Care; Expectations for the future of the nurses’ performance in Pre-Hospital Care, which resulted in nine subcategories. It is concluded that from these data, strategies can be thought of in the study scenario, with a view to the quality of Pre-Hospital Care.